Эволюция поэтического раздела в русской периодике начала ХХ века (заметки к теме) - Sobolev, Aleksandr (Wiener Slawistischer Almanach, 2023)
This article examines the metamorphosis of the poetry section of Russianjournals at the beginning of the twentieth century. It describes the dependence of periodicalsstructure on the printing process and demonstrates the emergence of the innovativeapproach to the journal layout. Such approach correlates with the modernists’growing attention to the internal structure of the poetic cycle and – more broadly – ofthe poetry collection. The author analyses cross-cultural parallels in the structure ofearly twentieth-century editions with the composition of almanacs of the Pushkin’stime. The archival materials demonstrate the secret springs of editorial policy of majorjournals of Russian modernism, primarily Moscow’s journal Vesy. In general, the evolutionof the poetry department appears as linear and technologically as well as conceptuallydetermined. At the pinnacle stands a journal composed of only poems in themanner of St. Petersburg’s Giperborei.